The Impact of Cognitive Impairment on Rehabilitation Outcomes among Geriatric Populations: A Systematic Review - Putra, I Gede Ari Permana; Verra, Verra (Indonesian Journal of Medicine, 2025)
Background: Cognitive impairment is a common issue in older adults and may significantly affect rehabilitation outcomes. Understanding the extent of its impact on medical rehabilitation is crucial for optimizing patient care and tailoring interventions for geriatric populations. Subjects and Method: This systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were performed using Google Scholar and PubMed to identify studies that examined the relationship between cognitive impairment and medical rehabilitation outcomes in the elderly. No restrictions were applied regarding publication dates or geographic regions, but only studies published in English were included. Out of 123 studies initially identified, 13 met the inclusion criteria, and 11 were included in the qualitative synthesis. Results: The analysis revealed that cognitive impairment negatively influenced rehabilitation outcomes in older adults. Patients with higher Mini-Mental State Examination (MMSE) scores demonstrated better functional recovery and greater improvements in rehabilitation. In contrast, those with significant cognitive impairment experienced reduced gains, highlighting a clear association between cognitive status and rehabilitation success. Conclusion: Cognitive impairment poses a substantial barrier to optimal rehabilitation outcomes among geriatric patients. These findings underscore the importance of incorporating cognitive assessment into rehabilitation planning and providing tailored interventions that address cognitive deficits. Enhancing rehabilitation strategies for individuals with cognitive impairment may improve functional recovery and overall quality of life in older populations.